2006
DOI: 10.1021/ef0602729
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of the Reaction of Partial Oxidation of Methane over Ni/La2O3 Catalyst

Abstract: The reaction of the partial oxidation of methane was investigated over Ni/La 2 O 3 catalysts prepared by impregnation. Two different reactors were used, a perfectly jet-stirred reactor and a fixed-bed reactor. The influences of nickel content, calcination temperature, reaction temperature, residence time, and contact time were investigated. Mechanistic information was derived from the comparison of the results obtained in both reactors. Characterization techniques such as X-ray diffraction, temperature-program… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
21
0
5

Year Published

2008
2008
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 47 publications
(27 citation statements)
references
References 46 publications
1
21
0
5
Order By: Relevance
“…For NiMgZn‐f catalyst the presence of MgO was not detected by XRD (Figure Ab). The reason may be that the MgO particles are highly dispersed or amorphous in nature, which are not detectable by the XRD analysis . Earlier reports also revealed that the particles with crystallite size less than 5 nm are not detectable by XRD analysis .…”
Section: Resultsmentioning
confidence: 98%
“…For NiMgZn‐f catalyst the presence of MgO was not detected by XRD (Figure Ab). The reason may be that the MgO particles are highly dispersed or amorphous in nature, which are not detectable by the XRD analysis . Earlier reports also revealed that the particles with crystallite size less than 5 nm are not detectable by XRD analysis .…”
Section: Resultsmentioning
confidence: 98%
“…51, 52 Several research groups have investigated the effect of metal loading on the COMR performance to optimize the metal content. In general, a large enhancement in COMR performance is observed with increasing metal content until a certain threshold;44, 46, 53 however, exceptions have been noted for certain catalyst systems 54. 55…”
Section: Comr Catalystsmentioning
confidence: 95%
“…[1][2][3] Two groups of catalyst have been used for methane activation to generate syngas: Ni-based catalysts and noble metal-based catalysts (Rh, Ru, Ir, Pd, Pt). In particular, nickel-based catalysts were widely adopted because of their low price and stability for extended periods when compared with noble metals with high cost and limited availability.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, from these studies, it appears that the oxidation state of nickel controls the mechanism and the product distribution, and CH 4 is oxidized by lattice oxygen in NiO or by active oxygen within the support. [1][2][3] Up to now, the reaction mechanism of the catalytic partial oxidation of methane still remains unclear and a unified viewpoint has not been reached. The reaction can proceed either via the direct way where CO and H 2 are produced as primary products 4,5 or via the indirect way where methane combustion produces CO 2 and H 2 O followed by steam and CO 2 reforming of the remaining methane.…”
Section: Introductionmentioning
confidence: 99%